Air Quality Measurements in Laying Hens Housing - Prodanov, Mirko; Radeski, Miroslav; Ilieski, Vlatko (Macedonian Veterinary Review, 2016)
Abstract Ensuring good environmental conditions of the poultry houses can be costly for the farmers, but without it losses due to poor bird health and performance due to poor air quality can be much more detrimental to net returns. The goal of this study was to investigate the variations in air quality in various areas inside the laying hen houses. Ten houses with laying hen conventional battery cages were measured for O2, H2S, CO, NH3, temperature, relative humidity, CO2, airflow and luminance. The results of the physical measures showed that temperatures in the houses were between 15.31–25.6°C, the relative humidity 48.03-81.12%, while the luminance rarely exceeded 8 lux. As for the gasses, the values for NH3 rarely exceeded 8 ppm, although at some measuring points it reached 26 ppm. O2 was generally at 20.9 %, and the levels of CO2 were very low. No presence of H2S and CO was detected. In this study it was concluded that the measurement of the air quality in a house can vary depending of the places this measures are taken. Multiple measurement points are important because they may make the staff aware of the problems connected to low ventilation and culmination of harmful gases. The air quality in different positions in the houses is of great importance not only for the animal welfare, but also for the safety of the staff.
Keywords: laying hens; ammonia; temperature; air quality